Self-Healing Behaviour of Pre-Cracked Pofa-Concretes in Different Curing Conditions - Khairul Anuar, Shahid; M. F. M., Jaafar; F. M., Yahaya (Faculty Mechanical Engineering, UMP, 2014)
The investigation of the effect of curing conditions on self-healing of pre-cracked concrete containing palm oil fuel ash (POFA)-concrete is presented. Concrete grade 30 was used and POFA cement replaced 10%, 20% and 30% of the total weight of ordinary Portland cement [1].The compressive strength was tested after 7, 28, 60 and 90 days cured in water in order to investigate the strength development of the POFA-concretes. In addition, the pre-crack (hairline crack) concrete was examined under compression load to determine the effectiveness of self-healing POFA-concretes after different curing conditions. Four types of curing condition, namely air, room temperature, wet and dry, and water curing were tested. An ultra-pulse velocity (UPV) test was performed after 7, 28, 60 and 90 days of curing to monitor the self-healing progress in the POFA-concrete. The results show that POFA-concrete witha 20% replacement level recorded the highest compressive strength. It was also revealed that the UPV readings increased significantly with increased curing age. The results showed that the selfhealing ability of pre-cracked POFA-concrete at 10% replacement level increases significantly for the water curing condition. From these findings, the optimum POFA replacement level was recorded at 20% for the strength, while inclusion of a 10% POFA replacement level was appropriate for self-healing concrete